The Discrimination Of Women As Seen In Hendrick Ibsen’s A Doll House - Nuraida Nuraida (Fakultas Sastra Universitas Ekasakti, 2017)
Problems in this thesis is about women, because of discrimination against women, there were resistance can be seen from the main character in the play A Doll's House and his struggle to obtain equality between women and men. Because women do not have to live forever under the pressure of men and not women may not work forever and forever no woman should take care of the children and her husband, like the main character Nora who willingly broke the law for the sake of getting the equality between men and women. This research method is a method of data collection, data analysis methods while the author does a systematic procedure with an understanding of the drama. Engineering data collection using the technique of qualitativ in finding relevant data with subject and author data analysis techniques using structural engineering by way of analyzing the drama based on the elements that shape it. In analyzing this drama author using psychology approach discusses the human personality which is the theory of Sigmund Freud includes the id, ego, superego man. Research results from the play A Doll House, the authors have found that the presence of the Suppression of freedom 1) inside the Doll House, 2) the existence of discrimination on the main character Nora in a doll's House, 3) as well as the struggle to be free from discrimination that had befallen him.